Harming, rescuing and the necessity constraint - Fabre, C (Springer Nature, 2021)
In The Morality of Defensive Force, Quong defends a powerful account of the grounds and conditions under which an agent may justifiably inflict serious harm on another person. In this paper, I examine Quong’s account of the necessity constraint on permissible harming - the RESCUE account. I argue that RESCUE does not succeed. Section 2 describes RESCUE. Section 3 raises some worries about Quong’s conceptual construal of the right to be rescued and its attendant duties. Section 4 argues that RESCUE does not deliver the verdicts which Quong wants. In those sections, I assume that the attacker is culpable for the threat he poses. Section 5 considers cases where the attacker, though responsible for the wrongful threat he poses and therefore liable to defensive force, has an epistemic justification for acting as he does and thus is not morally culpable. In his discussion of necessity, Quong does not explicitly such cases. I suggest that RESCUE does not operate in the same way when attackers are mistaken as when they are morally culpable.